Inside the law : Canadian law firms in historical perspective - Wilton, Carol (Essays in the history of Canadian law, 1996)
Law firms are important economic institutions in this country: they collect hundreds of millions of dollars annually in fees, they order the affairs of businesses and of many government agencies, and their members include some of the most influential Canadians. Some firms have a history stretching back nearly two hundred years, and many are over a century old. Yet the history of law firms in Canada has remained largely unknown. This collection of essays, Volume VII in the Osgoode Society's series of Essays in the History of Canadian Law, is the first focused study of a variety of law firms and how they have evolved over a century and a half, from the golden age of the sole practitioner in the pre-industrial era to the recent rise of the mega-firm. The volume as a whole is an exploration of the impact of economic and social change on law-firm culture and organization. The introduction by Carol Wilton provides a chronological overview of Canadian law-firm evolution and emphasizes the distinctiveness of Canadian law-firm history.